Interaction and Research of Biological Organic Fertilizer on Agricultural Soil Geological Improvement Preparation. Issue 3 (August 2020) - Yu, Wujiang; Lou, Jinyong; Song, Chunyan
Abstract: Based on the characteristics of bio-organic fertilizer material composition, the paper carried out an experimental study on the improvement of poor soil geology. Through the study of the geological background, stratigraphic characteristics and Quaternary characteristics of poor soil, and through petrification analysis, it was found that quartz in soil geology accounts for a large proportion, high silicate content, severe weathering, and insufficient fertility. At the same time, this article discusses the mechanism of bio-organic fertilizer to improve soil geology, and clarifies that the addition of sludge increases the content of soil geological organic matter, which is beneficial to increase the soil geological aggregate structure and humic acid content, and promote the optimization of geological ecosystem.